Shaping the Health and Foreign Policy Framework; Lessons Learned for Global Health Diplomacy in Iran - Sougand Tourani; Mohammad Salimi; Seyed Masood Mousavi (Shahid Sadoughi University of Medical Sciences, 2017)
Background: Today, peace and stability of health diplomacy in the Eastern Mediterranean region is faced with many challenges. In spite of extensive ignorance on health consequences in other fields and priorities of foreign policy, but foreign policy can be applied to improve health particularly in international health negotiations. Methods: To conduct this non-systematic review, articles relevant with the topic were selected from published texts and credible databases for investigation. Databases included Medline, web of science, Google scholar, Springer, PubMed, and all news websites. Results: Since issues of health are getting more political, having political view and mastering negotiation techniques is necessary. One of these conditions is multilateral negotiations, in which non-governmental organizations, advocacy groups, foundations, research centers, and private sectors get together to affect the present representatives of the member countries’ decision making about health topics and also to be part of the negotiation process.On the other hand, the international commitments of the Millennium Development goals, has put the health issue in a special position in international discussions. Further, epidemic growth of emerging diseases (such as AIDS, hepatitis, and influenza), immigration, and the sanctions have their impacts on the health sector, especially medicines and equipment, its serious impact on public health is also considered as an undeniable threat. Conclusion: In order to have effective application, health policy principles should be coordinated with other forms of diplomacy and also be placed at the top of all key stakeholders’ affairs including the Ministry of Health and other organizations effective on the health. Thus, to achieve the Millennium Development Goals and to escape from the problems based on the objectives of Vision 2025; this approach will solve many problems.